The Consumption and Wealth Effects of an Unanticipated Change in Lifetime Resources - Jappelli, Tullio; Padula, Mario (Management Science, 2016)
In 2000, Italy replaced its traditional system of severance pay for public employees with a new system. Under the old regime, severance pay was proportional to the final salary before retirement; under the new regime it is proportional to lifetime earnings. This reform entails substantial losses for future generations of public employees, in the range of €20,000–30,000, depending on seniority. Using a difference-in-difference framework, we estimate the impact of this unanticipated change in lifetime resources, on the current consumption and wealth accumulation of employees affected by the reform. In line with theoretical simulations, we find that each euro reduction in severance pay reduces the average propensity to consume by 3 cents and increases the wealth-income ratio by 0.32. The response is stronger for younger workers and for households where both spouses are public sector employees. This paper was accepted by Amit Seru, finance.